2007
DOI: 10.2967/jnumed.107.043794
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Myocardial  -Adrenergic Receptor Density in Relation to Increased Sympathetic Tone in Patients with Nonischemic Cardiomyopathy

Abstract: Cardiac sympathetic function plays an important role in the regulation of left ventricular (LV) function and the pathophysiology of LV dysfunction. 11 C-CGP-12177 ( 11 C-CGP) has been used to assess myocardial b-adrenergic receptor (b-AR) density in vivo using PET. The aim of this study is to measure myocardial b-AR density in patients with nonischemic cardiomyopathy and to compare the measurements with various standard parameters of heart failure (HF), particularly with presynaptic function assessed by 123 I-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…Taken together, our study findings suggest that the decrease of myocardial b-AR density implies the presence of higher cardiac sympathetic tone, which in turn predicts benefits from b-blocker treatment. Our findings have extended our own previous finding (8) and that of Spyrou et al (10) that decreased myocardial b-AR density is associated with left ventricular remodeling. Our results are in contrast to those of Gilbert et al, who found that carvedilol improved cardiac function without altering myocardial b-AR density in patients with heart failure (2), indicating that myocardial b-AR density may not predict the efficacy of b-blocker therapy.…”
Section: Myocardial B-ar Density As a Predictor Of Dlvef-carvedilolsupporting
confidence: 80%
See 3 more Smart Citations
“…Taken together, our study findings suggest that the decrease of myocardial b-AR density implies the presence of higher cardiac sympathetic tone, which in turn predicts benefits from b-blocker treatment. Our findings have extended our own previous finding (8) and that of Spyrou et al (10) that decreased myocardial b-AR density is associated with left ventricular remodeling. Our results are in contrast to those of Gilbert et al, who found that carvedilol improved cardiac function without altering myocardial b-AR density in patients with heart failure (2), indicating that myocardial b-AR density may not predict the efficacy of b-blocker therapy.…”
Section: Myocardial B-ar Density As a Predictor Of Dlvef-carvedilolsupporting
confidence: 80%
“…Myocardial b-adrenergic receptor (b-AR) density directly regulates left ventricular systolic function at rest and during dobutamine infusion (8,9). 11 C-CGP12177 PET has been established to allow us to measure myocardial b-AR density noninvasively (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There does not appear to be experimental values for the diffusion coefficient (D) for Dobutamine. One method of estimating D is from [11] /sec for diffusion in water. A value of 3.5x10 -10 m 2 /sec will be used.…”
Section: Resultsmentioning
confidence: 99%